Cost-effective track and trace technology for poor-quality chemotherapeutic pharmaceuticals in resource-limited countries: a review of the Chemotherapeutic Paper Analytical Device - Worku, Minichil Chanie; Limenh, Liknew Workie; Mekonnen, Biset Asrade; Anagaw, Yeniewa Kerie (Frontiers in Medical Technology, 2024)
Poor-quality medicines (substandard or counterfeit) can lead to treatment failure. There is a vast global imbalance in cancer treatment outcomes due to the difficulty of accessing quality chemotherapeutic products. Early diagnosis of cancer brings more hope for curative treatment of cancer and increases the demand for chemotherapeutic products. Consequently, it creates opportunities for unethical manufacturers and suppliers to develop substandard and/or counterfeit products. An ongoing review of cost-effective analytical methods is therefore paramount to tracking and tracing poor chemotherapeutic pharmaceutical products. Low- and middle-income country (LMIC) regulators lack safety equipment and standard operating procedures to handle chemotherapeutic products safely in the drug analysis laboratory and have limited capacity to perform post-marketing surveillance on these products. This review aimed to provide a compressive review of the Chemotherapeutic Paper Analytical Device (ChemoPAD). ChemoPAD is an important tool for quality screening of commonly used chemotherapeutic products in LMIC settings. It is an efficient, fast, simple, accessible, cost-effective, and transferable analytical method for verifying substandard and/or counterfeit chemotherapeutic products. Designed as a complete paper-based laboratory the size of a playing card, the ChemoPAD provides a promising solution for healthcare providers, patients, and other parties involved in post-marketing surveillance of chemotherapeutic products. Thus, in the near future, scientists could probably witness the use of the ChemoPAD technology platform to trace and track substandard and/or counterfeit chemotherapeutic products.